UNDERSTANDING CULTURE IN MEDICINE: ISSUES AND APPROACHES TO EFFECTIVE LEARNING - Divinagracia, Sheryl S.; Yuesti, Anik (International Journal of Applied Science and Sustainable Development (IJASSD), 2025)
In today’s increasingly diverse healthcare landscape, understanding cultural differences is essential for delivering effective, equitable and patient-centered care. This thesis explores the key issues and challenges faced by healthcare professionals in learning about cultural environments, including language barriers, stereotypes and lack of normal training. It also investigates various approaches used to enhance cultural competence such as immersive learning, cultural mediation and institutional training programs. Using a quantitative descriptive design based on a systematic review of related literature. This study aims to identify best practices in promoting cultural understanding in clinical settings. Findings from the research emphasize the importance of integrating cultural education into medical curricula and ongoing professional development. The study contributes to the growing body of knowledge in global health and medical education by highlighting practical strategies to improve cross-cultural communication and ultimately, patient outcomes.